A novel self-assembled nanocarrier-mediated dsRNA fungicide for broad-spectrum management of Rhizoctonia solani - Xiaojie Ding; Xinchun Li; Yan Li; Huiyan Guo; Kexin Cao; Mengnan An; Chong Zhang; Yuanhua Wu; He Liu; Rujun Zhou (Materials Today Bio)
Rhizoctonia solani Kühn is an important fungal pathogen that causes serious crop yield losses worldwide. The application of nanoscale strategies based on RNA interference (RNAi) represents an environmentally friendly and efficient approach for plant disease control. In this study, R. solani glycosyl hydrolase family 1 (RsGH1), which functions as a cell wall degrading enzyme (CWDE), and was screened as a prospective RNAi target gene for managing R. solani AG3 TB. Additionally, a novel nanosystem for loading and stabilization of double-stranded RNA (dsRNA) was developed. When the mass ratio of ε-poly-L-lysine (ε-PL) to carboxymethyl chitosan (CMCS) is 1:1, ε-PL can spontaneously conjugate with CMCS to form nanoscale spherical particles by electrostatic interaction, hydrogen bonding and Van der Waals forces. Compared with ε-PL alone, the introduction of CMCS resulted in more regular and uniform nanoparticles. dsRsGH1 spontaneously binds with ε-PL@CMCS, which is referred to as dsRsGH1@ε-PL@CMCS. ε-PL@CMCS protected dsRNA from RNase A degradation effectively. The combination of dsRsGH1 with ε-PL@CMCS remarkably improved the deposition and adhesion of dsRsGH1 droplets on Nicotiana tabacum (N. tabacum) leaves. The application of ε-PL@CMCS improved the RNAi efficiency of dsRsGH1 and prolonged its protective duration on crops. dsRsGH1 derived from R. solani AG3 TB also exhibited broad-spectrum activity against R. solani AG1-IA in rice and maize plants. In this study, a self-assembled multi-component nano-fungicide was designed based on dsRNA and nanocarriers. This work proposes an eco-friendly strategy to manage R. solani.